Determination of the Effects of Recycling on Polyolefin Matrix Composites - Unal, A.; Bekem, A.; Unal, A. R.; Guler, M. H. (DESTECH PUBLICATIONS, INC, 2013)
Thermoplastic composites, especially polyolefin ones, could not display strength values as high as thermoset composites due to their incompatibility between fibre-matrix interface. However, addition of compatibilizer could improve their mechanical performance nearly to the level of thermoset composites. Thus, applications and usages of thermoplastic composites were increased in recent years. This is the one of the reasons to take into consideration of recycling them. This study investigates the thermo-mechanical recycling of post-consumed E-glass fibre reinforced thermoplastic composites and their usage in similar to virgin chopped fibre reinforced composite materials. High density polyethylene ( HDPE), a group of thermoplastic polymer, was reinforced with the 4 mm length chopped E-glass fibre. HDPE matrix composites, which contain 5 wt% of maleic anhydride based compatibilizer, were recycled by a shredder. Obtained flakes have been molded by a laboratory scale press. Recycled composites were remanufactured up to 8 times cycling. Mechanical and physical properties of produced composites have been characterized. Tensile strength, flexural strength, impact strength were determined through mechanical tests. Calcination test was carried out to expose the fibre content and sieve analysis was also applied to these. Also fibre distribution behaviors in virgin and recycled composites were observed by microscopic investigation and mechanical performance of composites discussed according to this aspect. Effect of recycling on composites was evaluated for each type of composite separately.
Keywords: Recycling; polyolefin composites; E-glass fibre; HDPE; maleic anhydride; Materials Science